Weather, investor irrationality day-of-the-week anomaly: Case of Indonesia - Hooy, Chee-Wooi; Brahmana, Rayenda Khresna; Zamri, Ahmad (Springer Science + Business Media,LLC, 2012)
Finance is based on rational behavior assumption. Thus, the existence of day-of-weekend anomaly in the market can be the anti thesis of the assumption. Much research suggested the role of psychology as the explanation of this anomaly. However, it is rare to find a research investigating the relationship between psychology and day-of-week anomaly (DOWA). As one of the psychology factors is weather-induced mood, this research aims to investigate the relationship between weather cycle and DOWA. This paper used Indonesia average temperature level from 1999 up to 2009 for determining the proxy of moods; and found temperature level does not explain the market returns movements. Temperature level influences the DOWA implying the moods of investor establish the irrational behavior of the market. This result can be used as the explanation of irrationality behavior of investor on Monday. Further research is needed in term of investigating the relationship between psychology factors (need for cognition, heuristic bias, information ignorance, and other factors) and investor behavior.